Equitable technology development: A framework and methods for scientists and engineers - Jonathan Ensor; Steven Johnson; Daniel Vorbach; James Moir (Sustainable Futures)
Equity requires a rethinking of the processes and methods that applied scientists and engineers work through as they develop solutions that are simultaneously technical and social. By bridging insights from science and technology studies with critical analysis of participatory development practice, we propose a framework for understanding equitable technology development. We explore this through an illustrative case of water monitoring technology development, undertaken with scientists, engineers and communities in Vanuatu. Analysis suggests a typology of five methodological considerations that are significant for the practice of equitable technology development, locating equitable technology development as both a technical and an ethical challenge.